Geoinformatic background of geothermal energy utilization and its applications in East Hungary - Buday, Tamás; Buday-Bódi, Erika; Mcintosh , Richard William; Kozák, Miklós (Acta Geographica Debrecina Landscape & Environment series, 2016)
Powerful geothermal energy utilisation requires geoinformatic tools from potential surveying through the designing and setting of geothermal systems to certain operational tasks. However, practical data processing strongly depends on the elaboration of basic data and information, the type of the geothermal energy harvesting system and the character of the calculation demonstrated by case studies from East Hungary, in addition the usability of the resulted maps are also presented. Besides their usability for investors these maps could be refined in the location of the development before hydraulic/heat transport modelling.